Association Between Serum C- Reactive Protein With Migraine: A Case Control Study (Bangladesh Journal of Neuroscience, 2015)
Objective: The present case-control study was undertaken to find the association between serum level of CRP and attack of migraine.Methods: The study was carried out at the Headache Clinic and Outpatient Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of 2 years from January 2010 to December 2011. Migraine patients attending at the above mentioned places were enrolled as cases, while apparently healthy attendants of cases and other healthy persons, who did not have any history of migraine, were included as control. Based on predefined enrollment criteria, a total of 163 subjects were included in the study. Of them 87 were cases and 76 were controls. The serum levels of CRP of both cases and controls were measured and a serum level of > 6 mg/L was considered as raised/ elevated CRP. Levels of CRP were compared between groups (case and control) using appropriate statistical tests.Result: The findings of the study showed that the age and sex distribution of case and control groups were almost comparable. The behavioral factors like food or smoking habit and tobacco leaf chewing had no difference between the groups. Over 20% of migraine patients had abnormally high CRP as compared to 7.9% in the control group (p = 0.021). The migraine patients were 3(95% CI = 1.1 - 8.1) times more likely to be associated with raised CRP (> 6 mg/L) than their healthy counterparts. There were 7 migraine patients with aura and 80 without aura. The level of CRP was not found to be associated with type of migraine (with or without aura) (p = 0.960).Conclusion: Every one in five patients exhibits abnormally high CRP. The level of CRP does not vary whether the migraine is being associated with or without aura. The migraineurs carry higher risk of developing elevated CRP than their normal counterparts.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 1-8